ISOTOPE BEHAVIOUR OF STRONTIUM AND NEODYMIUM IN MINERALS OF GRANITE-AND SPINEL-CONTAINING PERIDOTITE XENOLITHS OF THE VITIM PLATEAU. FIRST DATA FROM THE USSR ON MANTLE INCLUSIONS - Ionov D.A.; Jaguz E. (My University, 1988)
The authors studied ten peridotite inclusions from basalts of the central Vitim Plateau namely eight granite-containing and one spinel-containing 1herzolite from recently discovered alkalic picrite tuff, thought to be of Eocene-Miocene age, and one spinel 1herzolite from the Pliocene Kandidushka volcano made up of basalt. The xenoliths, measuring 5 to 8 cm across, consisted of massive, coarse-grained, fairly fresh peridotite: the olivine was almost free of serpentinization, there was moderate kelyphitization of the granite, and whatever weak secondary alteration was present was found primarily along the grain boundaries. Study methods and results are discussed.
Keywords: Miocene; Eocene; Pliocene; Cenozoic::Paleogene::Eocene; Cenozoic::Neogene::Pliocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Плиоцен; Кайнозой::Палеоген::Эоцен; Кайнозой::Неоген::Миоцен